2019
DOI: 10.1111/epi.16282
|View full text |Cite
|
Sign up to set email alerts
|

Seizure specificities in patients with antibody‐mediated autoimmune encephalitis

Abstract: Accumulating data on patients with autoimmune encephalitis have shed light on specificities concerning clinical presentation and outcomes, which are dependent on the antigen targeted by the autoantibodies found in the patients’ cerebrospinal fluid or sera. Such specificities include seizure‐related clinical manifestations as well as the responsiveness to antiepileptic drugs. Although increased enthusiasm accompanies the discovery of novel antibodies and their associated clinical syndromes, several issues remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
72
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 107 publications
(364 reference statements)
13
72
1
2
Order By: Relevance
“…15 As seizure was one of the core symptoms of AIE, it is vital to distinguish "acute seizures" from "autoimmune epilepsy," which was defined as the "epilepsy" resulted directly from an immune disorder. 16,17 According to the definition of epilepsy mentioned above, our data showed that 21.3% patients with anti-NMDAR, anti-LGI1, and anti-GABA B R encephalitis may contribute to autoimmune epilepsy, and patients with anti-NMDA encephalitis described the similar probability. The proportion was in keeping with Liu et al's study, 7 in which 109 cases with anti-NMDAR encephalitis were enrolled, showing more than 80% of the whole cohort with acute seizures had their last seizure within 6 months from disease onset.…”
Section: Discussionmentioning
confidence: 75%
“…15 As seizure was one of the core symptoms of AIE, it is vital to distinguish "acute seizures" from "autoimmune epilepsy," which was defined as the "epilepsy" resulted directly from an immune disorder. 16,17 According to the definition of epilepsy mentioned above, our data showed that 21.3% patients with anti-NMDAR, anti-LGI1, and anti-GABA B R encephalitis may contribute to autoimmune epilepsy, and patients with anti-NMDA encephalitis described the similar probability. The proportion was in keeping with Liu et al's study, 7 in which 109 cases with anti-NMDAR encephalitis were enrolled, showing more than 80% of the whole cohort with acute seizures had their last seizure within 6 months from disease onset.…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, B*57:01 and C*06:02, which are known to be linked respectively to antibiotic-induced rash and psoriasis, were detected in patients presenting with these comorbidities [86]. Although cutaneous reactions related to antiepileptic drugs are a major concern in anti-LGI1 LE [87], no HLA associations have been yet described in this subgroup of patients [86].…”
Section: Limbic Encephalitis With Anti-leucine-rich Glioma-inactivatementioning
confidence: 99%
“…In the last few decades, the eld of autoimmune epilepsy has received increasing attention with the discovery of different subtypes of neural autoantibodies. 5,[16][17][18][19] In the latest 2017 epilepsy classi cation, autoimmune epilepsy has been recognized as a distinct entity by the International League Against Epilepsy. 20 Most patients with autoimmune epilepsy present with seizures, cognitive decline, and behavioral or psychiatric dysfunction.…”
Section: Discussionmentioning
confidence: 99%